Type-K Exponential Ordering with Application to Delayed Hopfield-Type Neural Networks - Bin-Guo Wang (Journal of Applied Mathematics)
Order-preserving and convergent results of delay functional differential equations without quasimonotone condition are established under type-K exponential ordering. As an application, the model of delayed Hopfield-type neural networks with a type-K monotone interconnection matrix is considered, and the attractor result is obtained.